Hydrogen Peroxide in Inflammation: Messenger, Guide, and Assassin - C. Wittmann; P. Chockley; S. K. Singh; L. Pase; G. J. Lieschke; C. Grabher (Advances in Hematology)
Starting as a model for developmental genetics, embryology, and organogenesis, the zebrafish has become increasingly popular as a model organism for numerous areas of biology and biomedicine over the last decades. Within haematology, this includes studies on blood cell development and function and the intricate regulatory mechanisms within vertebrate immunity. Here, we review recent studies on the immediate mechanisms mounting an inflammatory response by in vivo analyses using the zebrafish. These recently revealed novel roles of the reactive oxygen species hydrogen peroxide that have changed our view on the initiation of a granulocytic inflammatory response.